The Marketing Strategy Analysis of Beauty Soap Processed Etawa Crossbreed Goat’s Milk: Case Study at UD. Bali Sari Wangi, Banjar Belulang, Sepang Village, Busungbiu District, Buleleng Regency, Bali - Tutty Alwiah Abdullah; Budi Rahayu Tanama Putri; I Wayan Sukanata (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
This research aims to analyze the internal and external environmental factors of UD. Bali Sari Wangi which affects the marketing of goat's milk beauty soap determines UD. Bali Sari Wangi’s business position in the industry and formulating the right marketing strategy for UD. Bali Sari Wangi. This study is a case study conducted at UD. Bali Sari Wangi. The number of respondents was 33 people. Data is collected through observations, in-depth interviews and interviews with the help of questionnaires. The analysis used are 4, namely, 1) internal and external analysis of UD. Bali Sari Wangi; 2) the IE matrix; 3) SWOT analysis and 4) QSPM analysis. Ife and EFE analysis results of efforts obtained made by order (major strength) have not implemented a good marketing system (main weaknesses), the existence of suppliers who can meet the needs of raw materials (major opportunities) and diverse consumer demand (major threats). This research shows that UD's business position. Bali Sari Wangi is in cell IV (growing and built) in IE matrix with an IFE value of 3.08 and an EFE value of 2.94 with There are nine alternative strategies with the main priority strategy is to optimize the use of digital marketing and e-commerce.